Effect of wheat mill run on finishing pig performance - C H Fahrenholz; Keith C Behnke; David A Nichols (Kansas Agricultural Experiment Station Research Reports, 1988)
Finishing pigs were fed diets containing 0, 15, 30, or 45% wheat mill run (WMR) during cold and hot weather. Results indicate that 15% WMR can be included in finishing swine diets without adversely affecting pig performance. Apparent digestibilities of dry matter, gross energy, and crude fiber were lower (P<.05) for diets containing WMR than for the control. During cold weather incorporating up to 15% WMR in the diet may be economically justified, because there was no difference in cost of gain for pigs receiving the control or 15% WMR diets. During hot weather, cost of gain increased as the level of WMR in the diet increased.; Swine Day, Manhattan, KS, November 17, 1988
Keywords: Swine day; 1988; Kansas Agricultural Experiment Station contribution; no. 88-149-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 556; Swine; Wheat mill; Finishing pig; Performance